PENGARUH TANAMAN LIDAH MERTUA (Sansevieria strifasciata) SEBAGAI FITOREMEDIATOR LOGAM BERAT TIMBAL (PB) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CIPLUKAN (Physalis angulata L.) - Ana Alvia Dewi; Hidayat Bambang Setyawan (Jember University Press, 2020)
Ciplukan (Physalis angulata L.) is one of the plants included in the eggplant family and has fruit with a wrapper that resembles green leaves. The main constraints in cultivating ciplukan plants include Pb metal pollution caused by industry, mining waste, households, agriculture (organic fertilizer, manure, pesticides), paint, coal burning reduction, deposition from the atmosphere and other activities. Efforts are needed to overcome the Pb pollution in ciplukan taaman cultivation using phytoremediation plants such as tongue-in-law (Sansevieria trifasciata). The experiment was conducted at the Antirogo Green House, Sumbersari District, Jember Regency. The study used a completely randomized design (CRD) of 1 factor and 5 replications with 4 Pb metal concentration treatments (0 ppm, 10 ppm, 20 ppm and 30 ppm). The results showed that administration of Pb concentration at a concentration of 10 ppm Pb did not inhibit growth in plant height, and root length of ciplukan plants. whereas the administration of concentrations of 0 ppm, 10 ppm, 20 ppm and 30 ppm did not affect the yield of ciplukan plants. Keywords: phytoremediation, lead (Pb), concentration